Network approach to modelling and analysing failure propagation in high-speed train systems. Issue 4 (2nd October 2022) - Lin, Shuai; Jia, Limin; Zhang, Hengrun; Zhang, Pengzhu
Abstract : Since a high-speed train (HST) system is a complex integration of multiple minimum maintenance units (MMUs), a single faulty MMU can trigger a cascade of failures (specifically, in the form of fault spreading) and damage a substantial part of the HST system. To investigate the failure propagation in an HST system, the system is first abstracted to a weighted directed network composed of MMUs, connections and functional properties. Next, a failure propagation model is constructed from the perspective of load redistribution to mimic the process of failure propagation originating from a single failed MMU. The node reliability and the topological relationships among nodes are introduced to quantify the initial load and the capacity of nodes in the proposed model. Subsequently, this model is then applied to analyse the failure propagation in a China railway high-speed X (CRHX) HST under four types of attack strategies for a single MMU failure. The simulation results demonstrate that the proposed approach is highly effective in predicting the failure propagation, estimating the influence of the failure propagation on the HST system, and diagnosing large-scale failures. The results can provide guiding significance for maintenance personnel to develop strategies to reduce losses and optimise the management scheme.